The preventative effect of ramosetron on postoperative nausea and vomiting after total thyroidectomy - Lee, Dong Chul (The Korean Society of Anesthesiologists, 2011)
BACKGROUND: Postoperative nausea and vomiting (PONV) frequently develops in patients undergoing thyroidectomy, and propofol-based total intravenous anesthesia (TIVA) has been reported to reduce the incidence of PONV. The present study was undertaken to compare the effects of ramosetron on PONV in women following total thyroidectomy under TIVA. METHODS: One hundred and thirty women scheduled for thyroidectomy were allocated to either a control group (n = 65) or a ramosetron group (n = 65). Propofol in combination with remifentanil was used for TIVA in all patients. 2 ml of either intravenous saline (control group) or 0.3 mg of ramosetron (ramosetron group) were administered at the end of the surgery. Fentanyl-based patient-controlled analgesia was implemented for 48 h after surgery in all patients. The incidences and severities of PONV, pain scores, administrations of rescue antiemetics, and the side effects of the antiemetics were documented during the first 48 h after surgery. RESULTS: The incidences of complete response (no PONV, no rescue) in the control and ramosetron groups were 71% and 88%, respectively, during the first 6 h (P = 0.029), 85% and 94% during the next 6 to 24 h period (P = 0.155), and 97% and 95% during the last 24 to 48 h period (P = 1.00). During the first 6 h, the severity of nausea and the use of rescue antiemetic medication were significantly lower in the ramosetron group. CONCLUSIONS: Ramosetron was found to be effective at reducing the incidence and severity of postoperative nausea in women that underwent total thyroidectomy with propofol-based TIVA, especially during the first 6 hours postoperatively.